1996
DOI: 10.1111/j.1553-2712.1996.tb03399.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neuron–specific Enolase as a Prognostic Marker for Irreversible Brain Damage in Comatose Cardiac Arrest Survivors

Abstract: Objective: To assess the use of serum neuron-specific enolase (S-NSE) level as a noninvasive predictor of CNS injury irreversibility in comatose cardiac arrest survivors.Methods: An observational, prospective clinical study was performed in a community hospital ED and intensive care unit. All cardiac arrest survivors ( n = 52) with impaired neurologic status admitted between February 1994 and May 1995 were followed until return of consciousness (1) or death due to CNS failure (0). Serum samples for S-NSE deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 21 publications
5
26
0
1
Order By: Relevance
“…11 Therefore, recent attention focuses on biochemical markers of hypoxic brain damage. [13][14][15][16]22 To be an ideal marker for brain injury, the marker should be proved to be released from neurons or glial cells in experimental settings, for example cell cultures. Such proofs exist for NSE 32 but not for S-100.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Therefore, recent attention focuses on biochemical markers of hypoxic brain damage. [13][14][15][16]22 To be an ideal marker for brain injury, the marker should be proved to be released from neurons or glial cells in experimental settings, for example cell cultures. Such proofs exist for NSE 32 but not for S-100.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the fact that NSE, as in the present study, has shown promising results at later stages after cardiac arrest. [13][14][15][16] In contrast, release from blood cells in particular circumstances is not the case with S-100. The presence of S-100 in serum indicates cellular brain injury and damage to the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consensus on Science Serum neuronal-specific enolase (NSE) elevations are associated with poor outcome for comatose patients after cardiac arrest (LOE P1 905,906 ; LOE P2 852,894,897,[907][908][909][910][911][912][913][914][915][916][917][918][919][920] ; LOE P3 921,922 Serum S100 elevations are associated with poor outcome for comatose patients after cardiac arrest (LOE P1 905,906 ; LOE P2 894,897,907,913,915,917,918,[923][924][925][926][927][928] ; LOE P3 921 ).…”
Section: Biochemical Markers Als-pa-052a Als-pa-052bmentioning
confidence: 99%
“…The most extensively studied among these are glial protein S-100 beta( ) [45][46][47][48][49][50][51][52][53][54][55] , neuron-specific enolase (NSE) [56][57][58][59][60][61][62][63] , and myelin basic protein (MBP) 41,59,[64][65][66] Although some of these published studies suggest that these biomarkers correlate with degree of injury; conflicting results exist. [67][68][69][70][71][72][73][74][75] S100 is the major low affinity calcium binding protein in astrocytes 76 and it is considered a marker of astrocyte injury or death. It can also be found in non-neural cells such as adipocytes, chondrocytes, and melanoma cells.…”
Section: Status Of Biomarker Researchmentioning
confidence: 99%